An oxalic acid sensor based on platinum/carbon black-nickelreduced graphene oxide nanocomposites modified screenprinted carbon electrode - Kamolwich Income (2020)
© 2019, Korean Electrochemical Society. All rights reserved. A novel non-enzymatic oxalic acid (OA) sensor based on the platinum/carbon black-nickel-reduced graphene oxide (Pt/CBNi-rGO) nanocomposite is reported. The nanocomposites were prepared by the ethylene glycol reduction method. Their morphology and chemical composition were characterized by scanning electron microscopy (SEM), energy dispersive Xray spectroscopy (EDX) and transmission electron microscopy (TEM). The results clearly demonstrated the formation of the Pt/CB-Ni-rGO nanocomposite. The electrocatalytic activity of the Pt/CB-Ni-rGO electrode was investigated by cyclic voltammetry. It was determined that the appropriate amount of Pt enhanced the catalytic activity of Pt for oxalic acid electro-oxidation. Moreover, the modified electrode was determined to be highly selective for oxalic acid without interference from compounds commonly found in urine including uric acid and ascorbic acid. The chronoamperometric signal gave a wide linearity range of 20 μM-60 mM and the detection limit (3σ) was found to be 2.35 μM. The proposed method showed high selectivity, stability, and good reproducibility and could be used with micro-volumes of sample for the detection of oxalic acid. Finally, the oxalic acid content in artificial and control urine samples were successfully determined by our proposed electrode.